Penguatan Akuntabilitas Pengurus Koperasi Melalui Sosialisasi PERMENKOP Nomor 2 Tahun 2024 Di Koperasi Kabupaten Subang - Icih Icih; Nova Nursafitri; Nurul Adzra Nabilah; Muhamad Ramdan Gumelar; Vivian Nurul Insani; Nova Dwi Lestari (Pakis Journal Institute, 2024)
This Community Service Program aims to improve accounting literacy among cooperative administrators in Subang Regency, especially in understanding the differences between the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) and the Financial Accounting Standards for Private Entities (SAK EP) as regulated in the Regulation of the Minister of Cooperatives and SMEs Number 2 of 2024. This Regulation requires the implementation of new accounting policies in cooperatives no later than early 2025 to avoid administrative sanctions. The methods used in this program include the preparation, implementation, and evaluation stages. Preparation includes selecting participating cooperatives, namely Dekopinda Subang member cooperatives, and creating training modules. The implementation stage involves socializing accounting policies to participants through a combination of theory and practice, followed by pre-tests and post-tests to assess improvements in accounting literacy. The results of this program show an increase in participants' understanding of the new accounting policies, which are expected to improve the accountability and financial performance of cooperatives in Subang Regency.